The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/bpa.12134
|View full text |Cite
|
Sign up to set email alerts
|

Different Dynamics of Aquaporin 4 and Glutamate Transporter‐1 Distribution in the Perineuronal and Perivascular Compartments during Ischemic Stroke

Abstract: Aquaporin-4 (AQP4) and glutamate transporter-1 (GLT-1) represent the major water and glutamate astrocyte buffering gateways in the brain. Utilizing perilesional ischemic human cortices, we have performed here for the first time an integrative assessment on both AQP4 and GLT-1, and on their proximity to blood vessels and neurons. Counting the relative number of AQP4±/GLT-1±/glial fibrillary acidic protein± cells showed that double-positive variants were overall most frequent, and their number tended to decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…The co-localization of AQP4 and EAAT2 was diminished in striatal astrocytes of equilibrative nucleoside transporter 1 (ENT1) null mice compared with wild-type littermates [59,60]. In addition, it was also observed co-localization between AQP4 and GFAP expression [59,60] in the striatum of ENT1 null mice [60].…”
Section: Eaat2-aqp4 Interactions In Astrocytes and Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The co-localization of AQP4 and EAAT2 was diminished in striatal astrocytes of equilibrative nucleoside transporter 1 (ENT1) null mice compared with wild-type littermates [59,60]. In addition, it was also observed co-localization between AQP4 and GFAP expression [59,60] in the striatum of ENT1 null mice [60].…”
Section: Eaat2-aqp4 Interactions In Astrocytes and Parkinson's Diseasementioning
confidence: 99%
“…In the mammalian brain and spinal cord, AQP4 is co-localized with glutamate transporters of EAAT1 and EAAT2, as well as with Kir 4.1 in the astrocyte plasma membrane, which suggests that AQP4 could modulate K + and glutamate homeostasis [56]. Functionally, AQP4 and EAAT2 exist in astrocytic membranes, and are physically linked in a macromolecular complex of several brain regions and spinal cord [10,23,[57][58][59][60]. The immunohistochemical analysis of non-pathologic human CNS tissue of both, cortical and the spinal cord, reveal that EAAT2 is normally co-localized with AQP4 in gray matter astrocytes [10].…”
Section: Eaat2-aqp4 Interactions In Astrocytes and Parkinson's Diseasementioning
confidence: 99%
“…Five types of glutamate transporter have been found in the mammalian CNS. The two types expressed predominantly in glial cells, glutamate transporter-1 (GLT-1) and glutamate and aspartate transporter (GLAST), maintain glutamate homeostasis under physiological and pathological conditions (Mogoanta et al, 2014). Several studies have shown that up-regulation of glutamate transporter reduces cerebral infarct volumes and astrocyte swelling (Verma et al, 2010; Benesova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of GLT-1/EAAT-2 in the ischemic cortex reduces the size of lesion and improves the behavioral recovery (Harvey et al, 2011). The modulation of GLT-1/EAAT-2 has been shown to exert neuroprotection in various models of ischemic injury and motor neuron degeneration (Mogoanta et al, 2014). An attempt to explore the neuroprotective potential in cerebral ischemia/reperfusion injury was also made by using ceftriaxone, a GLT-1/EAAT-2 modulator which provides overwhelming evidence that modulation of GLT-1/ EAAT-2 protein expression and activity confers neuroprotection in cerebral ischemia/reperfusion injury (Verma et al, 2010).…”
Section: Strokementioning
confidence: 99%